From the Editor-in-Chief - Valery A. Sokolov (Моделирование и анализ информационных систем, 2019)
This issue of the journal “Modeling and Analysis of Information Systems” contains extended versions of selected reports presented at the 2nd International Scientific and Technical Conference “Modern Network Technologies 2018” (MoNeTec-2018), which was held on October 25-26, 2018 in Moscow, in Skolkovo Institute of Science and Technology (Skoltech). It was attended by representatives of the international scientific community, research units and corporations, start-ups, industry and business in Russia, development institutions and government bodies in the field of computer networks, network resources virtualization and cloud computing.The organizers and sponsors of the scientific IT forum were Skoltech, M.V. Lomonosov Moscow State University, Center for Applied Research of Computer Networks, Innopolis University, FGAU GNII ITT “Informika”, JSC “Concern Avtomatika”, Joint Institute for Nuclear Research, Institute of Electrical and Electronics Engineers (IEEE) and others.The conference was aimed at joint discussion of topical issues of research, development and implementation of modern telecommunication technologies based on the technology of building modern computer networks and information infrastructures SDN and NFV. SDN (Software Defined Networking) is a data network in which the network management level is separated from the data transfer devices and implemented programmatically. The key principles of software-configured networks are separation of data transfer and data management, centralization of network management using unified software, virtualization of physical network resources.Subjects of the conference reflected the following areas:- construction of modern computer networks;- service virtualization in SDN;- applications of modern network technologies;- organization of cloud computing;- applications of cloud technologies.The conference Program Committee includes leading scientists and developers from more than 10 countries of the world. The leadership of the Program Committee was carried out by:- R.L. Smeliansky, Corr. Member of the Russian Academy of Sciences, Professor of M.V. Lomonosov Moscow State University (Chairman);- A.P. Kuleshov, Academician of the Russian Academy of Sciences, President of the Skolkovo Institute of Science and Technology (Co-Chair).Currently, the world has begun to put into practice the key technologies of SDN and NFV for building modern computer networks and information infrastructures in general, but there are still many problems for study, development and implementation. The articles in this issue of the journal reflect to some extent these problems.